Attention attracts action in healthy participants: An insight into optic ataxia?. (April 2021) - Aguilar Ros, Anna; Mitchell, Alexandra G.; Ng, Yu Wa; McIntosh, Robert D.
Abstract: Patients with optic ataxia following lesions to superior parts of the posterior parietal cortex make large errors when reaching to targets in the peripheral visual field. These errors are characterised by a contraction, or attraction, towards the point of fixation. These patients also have a reduced ability to allocate visual attention away from the point of fixation, but it is unclear whether the core symptom of misreaching is related to these attentional problems. In neurologically-intact adults, we tested the effect of an attention-demanding dual-task performed at fixation upon visually-guided reaching to peripheral targets. The dual task was associated with delayed movement initiation, and a shortened deceleration phase of movement suggesting a reduced ability to benefit from online control. It also induced a small but consistent shift of reaching endpoints towards the side of fixation. Our experimental restriction of visual attention thus impaired both the programming and control of reaching, and induced a spatial pattern of errors that was qualitatively reminiscent of optic ataxia, albeit much less severe. These findings are consistent with a close functional link between attention and action in the healthy brain, and suggest that attentional disturbances could be a core component of optic ataxia following parietal lesions.